Observations on the ocurrence of pseudomonas aeruginosa in a sample of well water - CONROY, D.A. (Ars Pharmaceutica (Internet), 1961)
A sample of well water was examined, and it was found that the total bacterial count and the coliform count were of no significance in condemning the water as unsuitable for drinking purposes. Pseudomonas aeruginosa was found to be the predominating organism present and the possible relationship between this organism and thosel of the coliform group is considered. Reference to recent published work is made, in an attempt to show that the sample received should rightly be regarded as having been contaminated from faecal or sewage sources.